Optimal regulation of P2P lending for small and medium-sized enterprises - Naoko Nemoto; Bihong Huang; David J. Storey (Asian Development Bank Institute (ADBI), 2019)
Globally, the regulation of P2P lending has evolved significantly in recent years, with mostly beneficial effects on the diversification of funding for individuals and corporations. Regulatory responses have varied greatly between countries, and the characteristics of the markets that have emerged vary as a result. The purpose of this paper is to describe and evaluate the range of P2P lending systems on offer to small and medium-sized enterprises (SMEs) in several countries, considering different regulatory regimes. In some countries, there are problematic incentives for platforms that rate credit and originate loans without holding the risk of these loans. In addition, when investor returns are guaranteed by platforms, investors have no incentive to distinguish among risk categories. In several countries, notably the People's Republic of China, P2P platforms have engaged in fraudulent behavior and Ponzi-like schemes. On the other hand, stringent regulation in the United States has excessively impeded new entrants from providing competition to established platforms. Regulators should be mindful of these risks and others, while also seeking to capitalize on the benefits that the sector offers for providing new funding opportunities to SMEs. In our view, the United Kingdom can be suggested as an effective model to follow because of its tailor-made and flexible regulation.
Keywords: F34; F38; G23; 330; fintech; P2P lending; regulation